Rancang Bangun Monitoring dan Deteksi Dini Banjir Menggunakan Sensor Ultrasonik Berbasis NodeMcu Esp8266 Dengan Kendali Telegram (Studi Kasus: Komplek Safari, Jurang Mangu) - Ragil Alfikki; Yudi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The beautiful safari complex is a complex which is located at Jalan Kenari Raya, West Mangu Gorge, Pondok Aren District, South Tangerang City. Currently the beautiful safari complex has problems with extreme rainfall, flooding from rivers, and flooding due to clogged sewers, because floods always bring loss of property and loss of life, there are many ways to deal with flooding, but if certain parameters cannot be changed, it will still happen, such as lowlands and unadjusted rainfall. The method used the design of monitoring and early detection of floods using ultrasonik sensors based on nodemcu esp8266 with telegram control. This method is carried out by means of observation, interviews, library research and system design. The concept of this method is that this research is more focused and produces a very short cycle of development in informasimation retrieval until a flood detection tool is made. The results of the design of monitoring and early detection of floods using ultrasonik sensors based on nodemcu esp8266 with telegram control are designed to provide convenience in the process of disseminating informasimation related to flooding to residents.